1984
DOI: 10.1002/cne.902220107
|View full text |Cite
|
Sign up to set email alerts
|

An immunohistochemical study on the location of GABAergic neurons in rat septum

Abstract: Antisera against L-glutamate decarboxylase (GAD), the synthesizing enzyme of gamma-aminobutyric acid (GABA) were used to locate GABAergic neurons and nerve terminals in the septal complex of the rat by using the peroxidase-antiperoxidase method. Varying densities of immunoreactive terminals were observed in saline-treated rats but nerve cell bodies were only demonstrated after interventricular or intraseptal injections of colchicine. Small and medium-sized GAD-positive neurons were found in lateral septal nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
62
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(70 citation statements)
references
References 62 publications
8
62
0
Order By: Relevance
“…This is in keeping with the histochemical evidence of a substantial GABAergic innervation of the septal nuclei (2,3). Furthermore, stimulation of other septal neurotransmitter receptors (e.g., dopamine and P-endorphin) can decrease the hippocampal Ac The studies reported here were undertaken to correlate pharmacologically induced decreases in the hippocampal AcCho TR with changes in extinction of a food-reinforced lever-press response.…”
supporting
confidence: 79%
“…This is in keeping with the histochemical evidence of a substantial GABAergic innervation of the septal nuclei (2,3). Furthermore, stimulation of other septal neurotransmitter receptors (e.g., dopamine and P-endorphin) can decrease the hippocampal Ac The studies reported here were undertaken to correlate pharmacologically induced decreases in the hippocampal AcCho TR with changes in extinction of a food-reinforced lever-press response.…”
supporting
confidence: 79%
“…7C). These nuclei receive their major inputs from the hippocampus and are thought to produce ␥-aminobutyric acid (16). The triangular septal and septofimbrial nuclei provide 90% of all projections to the medial habenula via the stria medullaris, while the lateral septal cells are interneurons.…”
Section: Resultsmentioning
confidence: 99%
“…Brain neurons (347) and fibers (473) containing histamine had just been discovered. The histaminergic nucleus of the brain was identified as the TMN (473). It is involved in many aspects of brain function, including prominently food intake (508), which can be much affected by stress (112).…”
Section: Histaminementioning
confidence: 99%